The Role of Pokdarwis in Developing Tourism at Impos Beach, Medana Village, Tanjung Subdistrict, North Lombok Regency - Gani, Lalu Abdul; Bagiastra, I Ketut; Susanty, Sri (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
This research examines the role of Tourism Awareness Groups (Pokdarwis) in tourism development, focusing on Impos Beach in Medana Village, Tanjung District, North Lombok Regency. The study highlights the Pokdarwis Sejahtera as an informal institution formed by community members, playing a significant role in promoting Tourism Awareness and Sapta Pesona. The research aims to answer two key questions: (1) What is the role of Pokdarwis in tourism development at Impos Beach? (2) What are the supporting and inhibiting factors for Pokdarwis in tourism development at Impos Beach? Employing a qualitative descriptive approach, the study reveals that Pokdarwis Sejahtera serves as a government partner in tourism development, encourages community engagement and hospitality, and promotes Sapta Pesona. Supporting factors include community collaboration, equitable distribution of benefits, and willingness to work with Pokdarwis, while inhibiting factors involve limited capital, social jealousy, inadequate human resources, and tourists' low awareness of cleanliness